2018
DOI: 10.1177/1010428318776170
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-cancer activity of silymarin on oral cancer

Abstract: Silymarin, a standardized extract from milk thistle fruits has been found to exhibit anti-cancer effects against various cancers. Here, we explored the anti-cancer activity of silymarin and its molecular target in human oral cancer in vitro and in vivo. Silymarin dose-dependently inhibited the proliferation of HSC-4 oral cancer cells and promoted caspase-dependent apoptosis. A human apoptosis protein array kit showed that death receptor 5 may be involved in silymarin-induced apoptosis, which was also shown thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Clinically, silymarin showed anti-Parkinson and anti-Alzheimer effects (Ullah & Khan, 2018;Yaghmaei, Azarfar, Dezfulian, & Ebrahim-Habibi, 2014); in addition, anti-inflammatory effects of silymarin was significant in patients with arthritis (Hussain et al, 2009). Anticancer activity of milk thistle was observed in a variety of cancer cells (Agarwal, Agarwal, Ichikawa, Singh, & Aggarwal, 2006;Won et al, 2018). In mice with breast cancer, silymarin had anticancer activity and reduced tumor volume, consequently inhibited tumor growth.…”
mentioning
confidence: 99%
“…Clinically, silymarin showed anti-Parkinson and anti-Alzheimer effects (Ullah & Khan, 2018;Yaghmaei, Azarfar, Dezfulian, & Ebrahim-Habibi, 2014); in addition, anti-inflammatory effects of silymarin was significant in patients with arthritis (Hussain et al, 2009). Anticancer activity of milk thistle was observed in a variety of cancer cells (Agarwal, Agarwal, Ichikawa, Singh, & Aggarwal, 2006;Won et al, 2018). In mice with breast cancer, silymarin had anticancer activity and reduced tumor volume, consequently inhibited tumor growth.…”
mentioning
confidence: 99%
“…Silymarin also increased the level of cleaved caspase‐8 and truncated Bid in this cell line, resulting in cytochrome c accumulation. A careful analysis of two other oral cancer cell lines (YD15 and Ca9.22) also confirmed the role of death receptor 5/caspase‐8 activation in silymarin‐induced apoptosis (Won et al, ).…”
Section: Silymarin Anticancer Effects: What Has Been Discovered So Far?mentioning
confidence: 58%
“…Silymarin is able to inhibit HSC‐4 oral cancer cells proliferation and induce apoptosis in a dose‐dependent manner. An in vitro and in vivo study confirmed the anticancer activity of silymarin in oral cancer (Won et al, ). Through a study performed in salivary gland cancer‐derived MC3 and HN22 cells, it was found that silymarin and silibinin could induce mitochondria‐mediated apoptosis in salivary gland cancer cells, through modulating the proapoptotic protein, in a concentration‐ and time‐dependent manner.…”
Section: Silymarin Anticancer Effects: What Has Been Discovered So Far?mentioning
confidence: 72%
“…This also confirms the conclusions of our own research on pro-apoptotic properties of [6]-gingerol. Referring to anticancer effects of silymarin, it was noticed that silymarin inhibited oral tumor growth and proliferation of tumor cells [15,36].…”
Section: Discussionmentioning
confidence: 99%